STUDENT PERCEPTIONS IN FACING COVID-19 AT STIKES MUHAMMADIYAH LHOKSEUMAWE IN 2021 - Rahayu, Inong Sri; Musdarianto, Musdarianto (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2022)
Background: Students as someone who are considered educated must be able to give their views on the situation that occurs. Student perceptions are needed to find out the direction of student thinking regarding a problem face by this country, namely the Covid-19 pandemic. This study aims to find out in detail how the perceptions of students in dealing with Covid-19. Method: The method used in this research is descriptive method, where the number of samples is 150 sixth semester students of STIKes Muhammadiyah Lhokseumawe. Results: The research showed that the perceptions of student in the semester VI of the undergraduate nursing study program at STIKes Muhammadiyah Lhokseumawe were good (100%) with an average percentage score of 70.63%. Recommandation: This research is expected to be an evaluation of various parties in dealing with Covid-19. This research is also expected to be a reference for other researchers in analyzing and developing students' perceptions in dealing with the Covid-19 pandemic.